2007
DOI: 10.1136/ard.2007.079905
|View full text |Cite
|
Sign up to set email alerts
|

The metastasis associated protein S100A4: a potential novel link to inflammation and consequent aggressive behaviour of rheumatoid arthritis synovial fibroblasts

Abstract: The metastasis associated protein S100A4: a potential novel link to inflammation and consequent aggressive behaviour of rheumatoid arthritis synovial fibroblasts The metastasis associated protein S100A4: a potential novel link to inflammation and consequent aggressive behaviour of rheumatoid arthritis synovial fibroblasts AbstractThe metastasis-associated protein S100A4 belongs to the large family of S100 calcium-binding proteins that appear to play regulatory roles in diverse biological activities. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 83 publications
(98 reference statements)
2
39
0
Order By: Relevance
“…PDGFs are well known to be secreted by monocytes and progenitor cells and to stimulate proliferation of SMC and fibroblasts (3,46). SDF-1/CXCL12 is secreted by several cell types in response to hypoxia and has been reported to stimulate SMC proliferation (7,45). Consistent with this observation, we found that hypoxia further induces the potency of promitogenic activity of dR cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…PDGFs are well known to be secreted by monocytes and progenitor cells and to stimulate proliferation of SMC and fibroblasts (3,46). SDF-1/CXCL12 is secreted by several cell types in response to hypoxia and has been reported to stimulate SMC proliferation (7,45). Consistent with this observation, we found that hypoxia further induces the potency of promitogenic activity of dR cells.…”
Section: Discussionsupporting
confidence: 87%
“…In human PH patients, the presence of cells, expressing hematopoietic and inflammatory markers, has been documented both within and around the pulmonary vessel wall (22,23,42,74). In PAs of infants and children with PH, expression of S100A4 (also known as mts1), a calcium-binding protein associated with invasion, metastasis of cancer cells, and with augmented cell motility (5,45,54,71), has been documented, and the numbers of S100A4-expressing cells markedly increased with the severity of pulmonary vascular lesions (21,22). Recent studies in adults with idiopathic pulmonary arterial hypertension and familial pulmonary arterial hypertension have reported the presence of cells expressing hematopoietic and progenitor cell markers within the vessel wall, and cells exhibiting mesenchymal progenitor characteristics have been reported in remodeled PAs of patients with COPD (2,38,39,48,49,75).…”
Section: Discussionmentioning
confidence: 98%
“…[35][36][37] Therefore, patients with active inflammation processes, with coronary heart disease, or who had recently a heart attack were excluded. Patients who had a primary tumor of another entity in history or who developed a second primary tumor during follow-up were also excluded from this analysis.…”
Section: Classification Of Follow-up Patientsmentioning
confidence: 99%
“…Aberrant association of filamin-A with the prion protein PrPA correlates with worse prognosis in pancreatic cancer. A secreted variant of filamin-A in the blood correlates with highgrade astrocytomas and metastatic breast cancer (Ai et al, 2011;Alper et al, 2009;Anilkumar et al, 2003;Bedolla et al, 2009;Burton et al, 2010;Castoria et al, 2011;Kwon et al, 2008;Li et al, 2010b;Li et al, 2010c;Li et al, 2009;Loy et al, 2003;Smith et al, 2007;Sy et al, 2010;Uramoto et al, 2010;Zhou et al, 2011) Formins (Minamiya et al, 2005;Oslejskova et al, 2008) T-plastin (T-fimbrin) Microvilli of epithelial and mesenchymal cells Crosslinks F-actin into straight bundles T-plastin expression is enhanced in cisplatin-resistant human cancer cell lines (Hisano et al, 1996) L-plastin Crosslinks actin into orthogonal networks by forming tetramers. Forms a scaffold for signalling complexes and keeps SMAD3 or SMAD4 inhibited.…”
mentioning
confidence: 99%